Controlling Nutritional Status score does not predict patients' overall survival or hepatocellular carcinoma recurrence after deceased donor liver transplantation. Issue 3 (3rd February 2020) - Pravisani, Riccardo; Mocchegiani, Federico; Isola, Miriam; Lorenzin, Dario; Adani, Gian Luigi; Cherchi, Vittorio; Righi, Elda; Terrosu, Giovanni; Vivarelli, Marco; Risaliti, Andrea; Baccarani, Umberto
Abstract: Background: The Controlling Nutritional Status (CONUT) score is a newly developed laboratory‐derived immunonutritional score which has been validated as prognostic marker for survival and tumor recurrence in surgically treated patients with various tumor types, including hepatocellular carcinoma (HCC). The aim of the present study was to test the CONUT score performance in HCC patients treated with liver transplantation (LT). Methods: A retrospective study on a bi‐centers cohort of 280 HCC patients submitted to LT between 2006 and 2017 was performed. Indication to LT was limited to Milan criteria or UCSF criteria, defined by preoperative imaging. Results: Median pre‐LT CONUT score was 5 (interquartile range 3‐7). Overall patients' survival at 1, 3, and 5 years was 84%, 76.6%, and 68.3%, respectively. Multivariate analysis showed that HCC recurrence (hazard ratio [HR] = 1.987, P = .012] and pre‐LT neutrophil to lymphocyte ratio (NLR) (HR = 1.064, P = .003) were independent risk factors for reduced survival. Cumulative incidence of HCC recurrence at 1, 3, and 5 years was 5.1%, 11.5%, and 15.5%, respectively. Pre‐LT platelet‐to‐lymphocyte ratio (PLR) (subdistribution hazard ratio [SHR] = 1.086, P = .044], tumor max diameter (SHR = 1.695, P < .001), and bilobar tumor distribution (SHR = 6.892, P = .006) were independent risk factors for tumor recurrence. The CONUT score did not show any prognostic value. Conclusions: The CONUT score did not predict poor survival or tumor recurrence in LT recipients.